Umetnostno besedilo in jezikoslovje - Sajovic, Tomaž (Jezik in slovstvo, 2000)
The article discusses the reserved and hesistant attitude of linguistics towards literary language, which has a negative consequence also in their attitude towards non-literary texts. In developing his ideas, the author refers to J. R. Searle, J. Mukařovsky, R. Jakobson, H.-P. Bayerdörfer, B.Pogorelec, and to D. Pirjevec, G. W. F. Hegel, and M. Heidegger.
Keywords: tekstna lingvistika; umetnostno besedilo